The Plusiinae (Lepidoptera: Noctuidae) of Great Smoky Mountains National Park - Pogue, Michael G. (Zootaxa, 2005)
Seventeen species of Plusiinae have been found in Great Smoky Mountains National Park, in Tennessee and North Carolina, USA. These species are documented with adult images, description, flight period, abundance, elevation range, Park and general distribution, and larval hosts from the literature. Maps illustrate the known distribution of each species within the Park. Sixteen of the 17 species occur above 4,000 feet in elevation. The most diverse locality in the Park has 14 species.